The Effect Of Digital Competence On Employee Performance Through Artificial Intelligence Adaptation As An Intervening Variable - Muhamad Maulana; Gurawan Dayona Ismail; Nunung Ayu Sofianti (Efi); Yoyo Sudaryo; Asti Nur Aryanti (Green Publisher Indonesia, 2026)
This study aims to analyze the effect of Digital Competence, Technology Readiness, and Leadership Style on Employee Performance through the adaptation of Artificial Intelligence (AI) among employees at PT Sewangi Alam Nusantara. The study is motivated by the need to improve employee effectiveness, efficiency,and work quality in the digital era, where digital literacy,readiness of technological infrastructure, and adaptive leadership are key factors supporting adaptation to AI-based innovations. The research employed a quantitative approach with data collected through questionnaires distributed to 102 employees. Data analysis was conducted using Structural Equation Modeling (SEM)via Smart PLS 3.0 to examine both direct and indirect relationships among variables. The results indicate that Digital Competence (path coefficient = 1.740), Technology Readiness (2.731), and Leadership Style (1.844) positively affect Employee Performance. These three variables also contribute positively to AI Adaptation (0.534; 0.834; 1.063), which significantly mediates the improvement in employee performance (0.423), resulting in a total mediated effect of 0.917. The study concludes that a combination of digital competence, technology readiness, and adaptive leadership, reinforced by AI adoption, is a critical factor in enhancing employee productivity and performance. Practical implications include the need for digital literacy development, upgrading technological infrastructure,and applying leadership styles that support digital transformation to ensure optimal AI implementation in the workplace.